Closing the strategy-performance gap: The role of communication fit and distraction - Stephen Jeffrey; Heike Diller; Marina Fiedler (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
This paper seeks to present whether, and if so how, communication via websites can enhance or obstruct the link between strategy and performance. In doing so, we develop two forms of communication: fit and distraction. Fit refers to the congruence between external communication and strategy, while distraction implies the external communication of an alternative strategy. Using information asymmetry and contingency theory, we explain that greater fit can reduce information asymmetry and thus enhance the effects of a corporate strategy on performance. Using a unique dataset of German small enterprises, we find that fit and distraction have distinct effects on competitive positions such as the efficiency cost-leadership strategy and the quality differentiation strategy. External communication is generally shown to increase the effects of a quality strategy on performance. However, the wrong level of communication results in reduced performance. Therefore, organizations with a quality strategy should employ communication fit. In the case of efficiency strategy, the issue is more complex and efficiency strategy impacts performance only under certain conditions. Overall, we show that organizations are incentivized under certain circumstances to "walk the talk" - to practice what they preach - but are also not incentivized to implement strategies, which creates a moral hazard problem.
Keywords: 650; strategy; information asymmetry; communication; performance